Forces of nature : a history of Florida land conservation - Henderson, Clay, 1955- (University Press of Florida, 2022)
"In this comprehensive history of land conservation in Florida, Clay Henderson celebrates the individuals and organizations who made the state a leader in state-funded conservation and land preservation"-- Provided by publisher.
Keywords: Conservation of natural resources -- Florida -- History.; Land use -- Florida -- History.; Nature -- Effect of human beings on -- Florida.; Nature conservation -- Florida.; Conservation des ressources naturelles -- Floride -- Histoire.; Utilisation du sol -- Floride -- Histoire.; Êtres humains -- Influence sur la nature -- Floride.; Nature -- Conservation -- Floride.; HISTORY / United States / State & Local / South (AL, AR, FL, GA, KY, LA, MS, NC, SC, TN, VA, WV); NATURE / Regional.; Conservation of natural resources; Land use; Nature conservation; Nature -- Effect of human beings on; Florida; Electronic books.; History